Does the growth opportunities have an impact on hedging decision from own-stated companies in Indonesia? - Jovi Ostana Mangara Yudha; Reni Oktavia; Neny Desriani (Lighthouse Publishing, 2022)
This study aims to find out whether there is a relationship between growth opportunities and hedging. In the current era, all companies that have good growth opportunities will have a preference to expand their business activities to the international level. To reduce the risk of foreign exchange losses due to exchange rate fluctuations, the company will rely on hedging. However, this topic is still being debated because several previous research results have different results whether growth opportunity has an effect on hedging or not. This research uses a sample of state-owned companies listed on the Indonesia Stock Exchange from 2016 to 2020 whose data is obtained through the documentation method. The method used is purposive sampling and logistic regression analysis to assess the effect and possibility of hedging decisions used based on their growth opportunities. The results of this study indicate that growth opportunities have a significant positive effect on hedging. This is because state-owned companies have a preference to expand their operational activity, and this thing potentially need international transaction and companies will involve on exchange rate fluctuation, so to reduce the potential losses, companies will need hedging.